Blood, Guns, and Testosterone: Action Films, Audiences, and a Thirst for Violence - Donovan, Barna William (Rowman & Littlefield Publishers, 2009)
Since the early days of film, the representation of masculinity has changed considerably. In the beginning, men instinctively knew right from wrong. They rode to the rescue and saved the day in the nick of time to the admiration and gratitude of society. But over the decades, heroes have evolved from being larger than life and infallible to being cynical, washed up, unwanted outsiders. Violent content in these films also 'evolved'_from fistfights and gunplay to brutal attacks and nuclear explosions_repeatedly ramping up in frequency, intensity, and graphic depictions. But there is more to a violent film genre than violence, and Blood, Guns, and Testosterone: Action Films, Audiences, and a Thirst for Violence brings an entirely new understanding to the nature of such entertainment. In this book, Barna William Donovan examines masculinity and violence in action and adventure films and discusses how the most ardent fans of the genre incorporate this controversial form of entertainment into their lives. Donovan argues that far from becoming violent, the fans of the action film look at the genre as an artistic rumination on the nature of violence, good and evil, and the ever-changing definitions of manhood. At their very best, or most interesting at least, these films may even reflect on the nature of violence, on human nature, on aggression, and how a self-reflexive, moral society can deal with violence. And since so much of the violence of the world has always been perpetrated by men, action films_more often than not_are contemplations of the complicated meaning of manhood. In addition to fans of the genre, Blood, Guns, and Testosterone will appeal to scholars of film, history, popular culture, gender studies, and audience research.